(untitled) (Nigerian Journal of Technology, 2018)
The higher subscription, relative importance of voice calls, client’s complaints and economy depression that now make clients to get value for money paid and need for more revenue by mobile network operator (MNOs) justified this work. The objective of this work is to measure, analyse, evaluate the performance of MNOs, and to recommend ways to improving their quality of service (QoS). Drive test approach was used for the measurements and statistical methods for the analysis. Results of the analysis shows that the quality of Voice service offered by MNOs is not optimal and there is room for improved quality service. Based on the key performance indicators, the mobile operators did not perform up to expectation. There are differences in the quality of voice service offered across mobile network operator networks based on the time of the day and the area under consideration. MNO1, MNO2, MNO3 and MNO4 gave varying quality of service. MNO4 had absolutely no dropped calls and performed best and consistently gave a retainability ratio above the target. MNO1 performance metrics were below the key performance indicator thresholds given by the Nigerian Communication Commission. http://dx.doi.org/10.4314/njt.v37i3.21